Action Fluency in Parkinson’s Disease: A Mini-Review and Viewpoint - Gianelli, Claudia; Maiocchi, Carlotta; Canessa, Nicola (Frontiers in Aging Neuroscience, 2021)
Increasing evidence shows that the typical motor symptoms of Parkinson’s disease (PD) are often accompanied, if not preceded, by cognitive dysfunctions that are potentially linked to further complications of the disease. Notably, these cognitive dysfunctions appear to have a significant impact in the domain of action processing, as indicated by specific impairments for action-related stimuli in general, and verbs in particular. In this mini-review, we focus on the use of the action fluency test as a tool to investigate action processing, in PD patients. We discuss the current results within the embodied cognition framework and in relation to general action-related impairments in PD, while also providing an outlook on open issues and possible avenues for future research. We argue that jointly addressing action semantic processing and motor dysfunctions in PD patients could pave the way to interventions where the motor deficits are addressed to improve both motor and communicative skills since the early disease stages, with a likely significant impact on quality of life.